2020
DOI: 10.32479/irmm.9923
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Capital and Organizational Culture on Improving Organizational Performance

Abstract: To run their business, many companies uses various types of capital, financial, technological, as well as natural and human resource-based. In fact, optimal use of these kinds of capital do not guarantee that company will get maximum performance. There is still one important type of capital, namely social capital, which is an asset and instrument characterizing the interaction between employees and management. Social capital can also be conceptualized as a company's organizational culture. Here, interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Looking at previous studies, social capital has a positive effect on the career remuneration of organizational members and promotes the exchange of resources, product innovation, and corporate entrepreneurship activities within the company (Coleman, 2009;Hertati, 2015). Ashourizadeh et al (2014) verified the positive effects of social capital on SME growth and corporate performance, and Nuryanto et al (2020) confirmed that social capital promotes competitive advantage, which in turn has a positive effect on corporate performance. Social capital is divided into social capital outside the company that forms interactions with individuals or organizations outside the company and social capital inside the company centered on interactions between organizational members and departments.…”
Section: The Moderating Role Of Social Capitalmentioning
confidence: 66%
“…Looking at previous studies, social capital has a positive effect on the career remuneration of organizational members and promotes the exchange of resources, product innovation, and corporate entrepreneurship activities within the company (Coleman, 2009;Hertati, 2015). Ashourizadeh et al (2014) verified the positive effects of social capital on SME growth and corporate performance, and Nuryanto et al (2020) confirmed that social capital promotes competitive advantage, which in turn has a positive effect on corporate performance. Social capital is divided into social capital outside the company that forms interactions with individuals or organizations outside the company and social capital inside the company centered on interactions between organizational members and departments.…”
Section: The Moderating Role Of Social Capitalmentioning
confidence: 66%
“…China bused research of 112 enterprises and 269 surveys analysis the competitive advantage of CSR and social capital and indicated CSR indirectly permute competitive advantages for social capital that lead to performance of firms (Zhao, Meng, He, & Gu, 2019). Research focus on chemical manufacturing industry by used 97 respondents of manager of firms of Indonesia and indicated that positive and significant relationship between social capital and cultural Firm sustainability lead to human resource performance (Nuryanto, Mz, Sutawidjaya, & Saluy, 2020). China based research of mediator role of CSR and performance by used survey data of 206 chines firms and indicated green supplier integration both social and economic significant role for Firm sustainability (Cesar & Jhony, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, the structural dimension discusses the interactions between employees [68], with interactions mainly referring to the mode and network of connections among members, and the characteristics, strengths, and other attributes of these connections [69]. Moreover, the applications of the relational dimension in social capital focus on the quality of relationships, i.e., specific types of personal relationships established among group members through social interactions-and are dependent in terms of identification, trust, cooperation, obligation, and reciprocity norms [70][71][72].…”
Section: Social Capital Theorymentioning
confidence: 99%